Integrated care by community health workers in Malawi: Rehabilitation and blood pressure monitoring - Athenie Galvez; Jordan Waite; Kyle Jureidini; Kathryn C Nesbit (AIMS Public Health, 2021)
Background: Community health workers (CHWs) are essential providers of integrated care for people in low-resourced settings with a high burden from noncommunicable diseases (NCDs).